A SENI DAN REKOGNISI TUNAGRAHITA: SENI VISUAL SEBAGAI TERAPI PENGEMBANGAN FUNGSI KOGNITIF ANAK TUNAGRAHITA - Putri, Antonia Kristiana Dian; Vashti Bestari Kustedja, Elaine (Integritas Terbuka: Peace and Interfaith Studies, 2023)
This research aims to deepen and to apply visual arts therapy, especially fine arts, as intervention method to improve the cognitive function of children with down syndrome and intellectual disability. The case of intellectual disability, especially down syndrome, increases in Indonesia. Children with down syndrome experience delays in growth, development, and independence compared to their peers. Children with intellectual disabilities are believed to benefit from visual arts therapy as a means of self-development and rehabilitation. Four kids participated in this study; two of them had down syndrome and the other two were intellectually disable. Analysis was carried out by observing the development of the images produced by the kids from three separated sessions. The findings demonstrate positive developments in every kid’s drawing skill, expression and artistic exploration. This research also discusses the application of SAVI method (Somatic, Auditory, Visually, Intellectually) in children's art activities. Children with intellectual disability benefit from the development of creativity and cognitive function through visual arts therapy that employs the SAVI technique, with a particular emphasis on visual features. In conclusion, children with down syndrome and intellectual disability can benefit greatly from visual arts treatment in terms of their cognitive performance. Parents’ and facilitators’ roles are crucial in supporting children’s development process. It is proposed that this study would positively impact the creation of an all-encompassing therapeutic strategy to raise the standard of living for kids with disabilities.